Teknik Relaksasi Nafas Dalam Penanganan Masalah Nyeri Kepala Pada Pasien Hipertensi Diruangan Pattimura RST Ambon - Yerry Soumokil; Siti Rochmaedah; Demelza Ester Bulubili (Jurnal Sains dan Kesehatan, 2023)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a state of sufficient rest/calm. One of the non-pharmacological therapies to reduce pain is a deep breathing relaxation technique consisting of slow, rhythmic chest and abdominal breathing which has the benefit of relieving acute and chronic pain by doing it constantly.